2022
DOI: 10.1007/s10439-022-03026-8
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Fit Evaluation of Additively Manufactured Face Coverings

Abstract: In response to the respiratory protection device shortage during the COVID-19 pandemic, the additive manufacturing (AM) community designed and disseminated numerous AM face masks. Questions regarding the effectiveness of AM masks arose because these masks were often designed with limited (if any) functional performance evaluation. In this study, we present a fit evaluation methodology in which AM face masks are virtually donned on a standard digital headform using finite element-based numerical simulations. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Indeed, the median [fist quartile; third quartile] values of TFE measured without nosepiece at the three flow rates were 12 [9,15] %, 21 [17,29] % and 32 [25,39] % respectively. With the nosepiece in place, the same group of masks tested in identical testing conditions presented TFE values of 15 [13,19] %, 28 [22,33] % and 40 [31,45] %. The comparison of TFE values obtained with and without nosepiece over the 26 tested masks indicated that a significant increase in TFE was achieved when the nosepiece was present (p<0.05, Wilcoxon rank-sum test).…”
Section: The Role Of the Nosepiecementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the median [fist quartile; third quartile] values of TFE measured without nosepiece at the three flow rates were 12 [9,15] %, 21 [17,29] % and 32 [25,39] % respectively. With the nosepiece in place, the same group of masks tested in identical testing conditions presented TFE values of 15 [13,19] %, 28 [22,33] % and 40 [31,45] %. The comparison of TFE values obtained with and without nosepiece over the 26 tested masks indicated that a significant increase in TFE was achieved when the nosepiece was present (p<0.05, Wilcoxon rank-sum test).…”
Section: The Role Of the Nosepiecementioning
confidence: 99%
“…ASTM has recently provided a framework for the specifications of barrier face covering performance [18]. However, the document recognizes that no accepted methodologies were defined to measure total filtration efficiency from loose-fitting face masks and face coverings despite recent studies have demonstrated the relation of mask design features and fitting with air leakage and overall filtration performance [19], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation